Methacrylic resin, method for producing same, resin composition, and resin film

By using specific non-nitrile-based azo polymerization initiator and chain transfer agent when synthesizing methacrylic resins, the polymerization conditions and terminal double bond ratio are controlled, and the problem of reducing the thermal stability of the resin is solved, achieving high thermal stability and Excellent glass transition temperature and mechanical properties.

CN119451999APending Publication Date: 2025-02-14KANEKA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380044609.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-07
Filing Date
2023-06-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When synthesizing methacrylic resins, the thermal stability of the obtained resin is reduced due to the different types and conditions of the polymerization initiator.

Method used

In the presence of a non-nitrile azo polymerization initiator and a chain transfer agent, the monomer mixture with a content of 98% by mass or more of methyl methacrylate is polymerized at 100°C to control the polymerization conversion to 90% or more than 90%. , use specific non-nitrile-based azo polymerization initiators such as 2,2'-azobis(isobutyric acid) dimethyl ester and 1,1'-azobis(cyclohexane carboxylate) and control The proportion of terminal double bonds is less than 0.020 mol%.

Benefits of technology

High thermal stability of methacrylic resin was achieved, the thermal weight loss rate of the resin for 15 minutes exposed at 280°C was less than 2.5%, and the glass transition temperature and mechanical properties of the resin were improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451999A_ABST
    Figure CN119451999A_ABST
Patent Text Reader

Abstract

Provided are: a methacrylic resin in which the proportion of structural units derived from methyl methacrylate is 98% by mass or more and the syndiotacticity represented by triad is 55% or more; the methacrylic resin contains a terminal structure represented by formula (1) derived from a polymerization initiator, and the ratio of a terminal double bond to a structural unit derived from methyl methacrylate is less than 0.020 mol%. In formula (1), R1, R2, and R3 each independently represent an alkyl group, a substituted alkyl group, an ester group, or an amide group. In this connection, at least one of R1, R2, and R3 represents an ester group or an amide group. Also provided are a resin composition containing the methacrylic resin, a resin film containing the methacrylic resin, and a polarizing plate and a display device obtained using the resin film. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a methacrylic resin and a method for producing the same, a resin composition and a resin film. Background Art

[0002] Methacrylic resins are widely used in various fields due to their excellent transparency, weather resistance, processability, etc. In particular, resin films obtained by molding methacrylic resins are also used for optical applications such as display devices due to their excellent optical properties. The methacrylic resins are produced by, for example, polymerizing a monomer mixture containing methyl methacrylate as a main component in the presence of a polymerization initiator and a chain transfer agent (see, for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2019 / 088025 Summary of the invention

[0006] Problem that the invention aims to solve

[0007] However, the present inventors have found through studies that the thermal stability of the obtained methacrylic resin decreases depending on the conditions such as the type of polymerization initiator used in the synthesis of the methacrylic resin.

[0008] An object of the present invention is to provide a methacrylic resin having excellent thermal stability and a method for producing the same, a resin composition containing the methacrylic resin, a resin film containing the methacrylic resin, and a polarizing plate and a display device obtained by using the resin film.

[0009] Solutions for solving problems

[0010] Specific means for solving the above-mentioned problems include the following embodiments.

[0011] <1> A methacrylic resin, wherein the ratio of structural units derived from methyl methacrylate is 98% by mass or more,

[0012] The syndiotacticity expressed as triad is 55% or more,

[0013] The methacrylic resin includes a terminal structure represented by the following formula (1) derived from a polymerization initiator,

[0014] The ratio of the terminal double bonds to the structural units derived from methyl methacrylate is less than 0.020 mol %.

[0015]

[0016] (Where R 1 , R 2 and R 3 Each independently represents an alkyl group, a substituted alkyl group, an ester group or an amide group. 1 , R 2 and R 3 At least one of represents an ester group or an amide group. 1 , R 2 and R 3 The two of them may be bonded to each other to form an alicyclic structure. * represents a connecting bond to a structural unit derived from a monomer. )

[0017] <2> according to <1> The methacrylic resin has a thermal weight loss rate of less than 2.5% when exposed to 280° C. for 15 minutes in a nitrogen atmosphere.

[0018] <3> according to <1> or <2> The methacrylic resin described above has a terminal structure represented by the formula (1) derived from at least one selected from the group consisting of 2,2'-azobis(isobutyric acid)dimethyl ester and 1,1'-azobis(cyclohexanecarboxylic acid methyl ester).

[0019] <4> according to <1> ~ <3> The methacrylic resin described above has a weight average molecular weight (Mw) of 50,000 to 200,000 as measured by gel permeation chromatography (GPC).

[0020] <5> according to <1> ~ <4> The methacrylic resin described above has a ratio (Mw / Mn) of a weight average molecular weight (Mw) to a number average molecular weight (Mn) measured by gel permeation chromatography (GPC) of 1.6 to 2.5.

[0021] <6> A method for producing a methacrylic resin, comprising:

[0022] A polymerization step of polymerizing a monomer mixture containing 98% by mass or more of methyl methacrylate at 100° C. or less in the presence of a non-nitrile azo polymerization initiator and a chain transfer agent until the polymerization conversion rate reaches 90% or more,

[0023] The amount of the chain transfer agent used is 0.10 mol% or more relative to the total amount of the monomer mixture.

[0024] The ratio of the total molar amount of the chain transfer agent to the total molar amount of the non-nitrile azo polymerization initiator is 2.0 or more.

[0025] <7> according to <6> The method for producing a methacrylic resin comprises the step of performing aqueous polymerization in the polymerization step.

[0026] <8> according to <6> or <7> In the method for producing a methacrylic resin, the non-nitrile azo polymerization initiator comprises at least one selected from 2,2'-azobis(isobutyric acid)dimethyl ester and 1,1'-azobis(cyclohexanecarboxylic acid methyl ester).

[0027] <9> A resin composition comprising <1> ~ <5> The methacrylic resin described above.

[0028] <10> according to <9> The resin composition contains an ultraviolet absorber.

[0029] <11> A resin film comprising <1> ~ <5> The methacrylic resin described above.

[0030] <12> according to <11> The resin film contains an ultraviolet absorber.

[0031] <13> according to <11> or <12> The resin film is a polarizer protective film.

[0032] <14> A polarizing plate is a polarizing plate <11> ~ <13> The resin films described above are stacked.

[0033] <15> A display device comprising <14> The polarizing plate.

[0034] Effects of the Invention

[0035] According to the present invention, there are provided a methacrylic resin having excellent thermal stability, a method for producing the same, a resin composition containing the methacrylic resin, a resin film containing the methacrylic resin, and a polarizing plate and a display device using the resin film. DETAILED DESCRIPTION

[0036] Hereinafter, specific embodiments obtained by applying the present invention will be described in detail. Unless otherwise specified, the symbol "to" indicating a numerical range is used to mean that the lower limit and the upper limit of the range are included.

[0037] <Methacrylic resin>

[0038] In the methacrylic resin described in the present embodiment, the proportion of the structural unit derived from methyl methacrylate is 98% by mass or more, and the proportion of the structural unit derived from the monomer other than methyl methacrylate is 2% by mass or less. In the methacrylic resin described in the present embodiment, the proportion of the structural unit derived from methyl methacrylate is preferably 99% by mass or more, and more preferably 100% by mass (i.e., homopolymer of methyl methacrylate). It should be noted that the structural unit derived from methyl methacrylate is represented by the following formula.

[0039]

[0040] Examples of monomers other than methyl methacrylate include alkyl acrylates such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate; aryl acrylates such as phenyl acrylate; cycloalkyl acrylates such as cyclohexyl acrylate and norbornyl acrylate; alkyl methacrylates other than methyl methacrylate such as ethyl methacrylate, propyl methacrylate, and butyl methacrylate; aryl methacrylates such as phenyl methacrylate; cycloalkyl methacrylates such as cyclohexyl methacrylate and norbornyl methacrylate; aromatic vinyl compounds such as styrene and α-methylstyrene; acrylamide; methacrylamide; acrylonitrile; methacrylonitrile, and the like.

[0041] The methacrylic resin described in this embodiment has a syndiotacticity (rr) expressed by a triad of 55% or more, preferably 56% or more, and more preferably 57% or more. If the syndiotacticity (rr) expressed by a triad is 55% or more, the glass transition temperature (Tg) of the methacrylic resin tends to be higher and the heat resistance tends to be improved. The upper limit of the syndiotacticity (rr) is not particularly limited, but from the viewpoint of the molding temperature, the toughness of the molded body, and the secondary processability, it is preferably 67% or less, more preferably 65% ​​or less, and further preferably 63% or less.

[0042] Syndiotacticity (rr) is the ratio of two chains (diads) of a chain of three consecutive structural units (triads) that are both racemic (rr). It should be noted that in the chains (diads) of structural units in polymer molecules, the same stereo configuration is called meso, and the opposite is called racemo, which are expressed as m and r, respectively.

[0043] The syndiotacticity (rr) can be calculated as described in the Examples below: The syndiotacticity (rr) is measured in deuterated chloroform at 22°C and 16 accumulation times. 1H-NMR spectrum, from which the area (X) of the region of 0.60 to 0.95 ppm and the area (Y) of the region of 0.60 to 1.25 ppm when tetramethylsilane (TMS) was set to 0 ppm were measured, and calculated using the formula (X / Y)×100.

[0044] In addition, the glass transition temperature (Tg) of the methacrylic resin described in this embodiment is preferably 120° C. or higher, more preferably 121° C. or higher, and further preferably 122° C. or higher. The upper limit of the glass transition temperature (Tg) is not particularly limited, but is preferably 135° C. or lower, and may be 130° C. or lower, from the viewpoint of the molding temperature and the secondary processability of the molded body.

[0045] The glass transition temperature (Tg) in this specification is a midpoint glass transition temperature obtained from a DSC curve, and is measured by the method described in Examples below.

[0046] It should be noted that the syndiotacticity (rr) and glass transition temperature (Tg) of the methacrylic resin can be controlled by adjusting the polymerization temperature when synthesizing the methacrylic resin. For example, lowering the polymerization temperature is preferred for increasing the syndiotacticity (rr) of the methacrylic resin and increasing the glass transition temperature (Tg). In addition, the glass transition temperature (Tg) can also be controlled by adjusting the molecular weight of the methacrylic resin.

[0047] The methacrylic resin according to the present embodiment includes a terminal structure represented by the following formula (1) derived from a polymerization initiator.

[0048]

[0049] (Where R 1 , R 2 and R 3 Each independently represents an alkyl group, a substituted alkyl group, an ester group or an amide group. 1 , R 2 and R 3 At least one of represents an ester group or an amide group. 1 , R 2 and R 3 The two of them may be bonded to each other to form an alicyclic structure. * represents a connecting bond to a structural unit derived from a monomer. )

[0050] Examples of the alkyl group include linear or branched alkyl groups having 1 to 6 carbon atoms. Examples of the substituent group that the alkyl group may have include a hydroxyl group, a carboxyl group, an alkoxy group, and a halogen atom.

[0051] Examples of the ester group include -COOR 4 The group shown. 4 It represents an alkyl group having 1 to 6 carbon atoms, which may have a substituent such as a hydroxyl group, a carboxyl group, an alkoxy group or a halogen atom.

[0052] Examples of the amide group include -C(O)NR 5 The group shown. 5 It represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group or an alkenyl group having 2 to 6 carbon atoms, and may have a substituent such as a hydroxyl group, a carboxyl group, an alkoxy group or a halogen atom.

[0053] The terminal structure represented by the above formula (1) can be introduced into the molecule of the methacrylic resin by using a non-nitrile azo polymerization initiator represented by the following formula (2) when synthesizing the methacrylic resin. 1 , R 2 and R 3 The same meaning as in the above formula (1). By using such a non-nitrile azo polymerization initiator, the thermal stability of the obtained methacrylic resin tends to be improved compared to the case where a polymerization initiator other than the non-nitrile azo polymerization initiator (e.g., a nitrile azo polymerization initiator) is used. In addition, the non-nitrile azo polymerization initiator tends to have lower toxicity of the initiator itself and the decomposition product than the nitrile azo polymerization initiator, and is also preferred in this respect.

[0054]

[0055] Examples of the non-nitrile azo polymerization initiator represented by the formula (2) include 2,2'-azobis(isobutyric acid) dimethyl ester, 1,1'-azobis(cyclohexanecarboxylic acid methyl ester), 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide), 2,2'-azobis{2-methyl-N-[2-(1-hydroxyethyl)]propionamide}, and 2,2'-azobis{2-methyl-N-[2-(1-hydroxybutyl)]propionamide}. Among these, at least one selected from 2,2'-azobis(isobutyric acid) dimethyl ester and 1,1'-azobis(cyclohexanecarboxylic acid methyl ester) is preferred from the viewpoints of half-life temperature, cost, and the like.

[0056] In addition, in the methacrylic resin according to the present embodiment, the ratio of the terminal double bonds to the structural units derived from methyl methacrylate is less than 0.020 mol%, preferably less than 0.015 mol%, more preferably less than 0.010 mol%, and further preferably less than 0.006 mol%. When the ratio of the terminal double bonds is within the above range, the thermal stability of the methacrylic resin tends to be improved.

[0057] The methacrylic resin described in this embodiment can be manufactured by a free radical polymerization method as shown in the manufacturing method described later. The methacrylic resin manufactured by the free radical polymerization method contains terminal double bonds generated by a disproportionation termination reaction in polymerization, a hydrogen abstraction reaction of a monomer based on a polymerization initiator, etc. The terminal double bonds affect the thermal stability of the resin, so it is preferred that the proportion is small. The proportion of the terminal double bonds is controlled by the method described later. If it can be reduced to a range of 0.001 mol% or more and less than 0.020 mol%, there is a tendency that the thermal stability of the methacrylic resin is greatly improved.

[0058] The ratio of the terminal double bond to the structural unit derived from methyl methacrylate can be calculated as described in the Examples below: The ratio of the terminal double bond to the structural unit derived from methyl methacrylate can be calculated as follows ... 1 H-NMR spectrum, from which the total area (X) of the peaks derived from the terminal double bonds of the methacrylic resin (5.47 to 5.53 ppm and 6.21 ppm) and the area (Y) of the peak derived from the α-methyl group of the methacrylic resin (0.5 to 1.25 ppm) were measured, and calculated using the formula [(3×X) / (2×Y)]×100.

[0059] It should be noted that the proportion of terminal double bonds in the methacrylic resin can be controlled by adjusting the amounts of the polymerization initiator and chain transfer agent used, the polymerization temperature, the polymerization time, etc. when synthesizing the methacrylic resin. For example, reducing the amount of the polymerization initiator, increasing the amount of the chain transfer agent, lowering the polymerization temperature, and extending the polymerization time are preferred for reducing the proportion of terminal double bonds.

[0060] As described above, the methacrylic resin according to the present embodiment has excellent thermal stability. The thermal weight loss rate of the methacrylic resin according to the present embodiment when exposed to a nitrogen atmosphere at 280° C. for 15 minutes is preferably less than 2.5%, and more preferably less than 2.3%. The thermal weight loss rate is measured by the method described in the examples described below.

[0061] The weight average molecular weight (Mw) of the methacrylic resin according to the present embodiment is preferably 50,000 to 200,000, and more preferably 90,000 to 150,000. If the weight average molecular weight (Mw) of the methacrylic resin is 50,000 or more, the mechanical properties of the obtained molded product tend to be improved, and if the weight average molecular weight (Mw) of the methacrylic resin is 200,000 or less, the moldability tends to be improved.

[0062] In addition, the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the methacrylic resin described in this embodiment, that is, the dispersion (Mw / Mn), is preferably 1.6 to 2.5, and more preferably 1.7 to 2.2. When the dispersion (Mw / Mn) of the methacrylic resin is 1.6 or more, the fluidity of the methacrylic resin tends to be improved and molding is easy, and when the dispersion (Mw / Mn) of the methacrylic resin is 2.5 or less, the mechanical properties such as impact resistance, toughness, and bending resistance of the obtained molded body tend to be improved.

[0063] The weight average molecular weight (Mw) and number average molecular weight (Mn) in this specification are values ​​calculated in terms of standard polystyrene measured by gel permeation chromatography (GPC), and are measured by the method described in the examples described later.

[0064] It should be noted that the weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin can be controlled by adjusting the type and amount of the polymerization initiator and chain transfer agent used in synthesizing the methacrylic resin.

[0065] The methacrylic resin described in the present embodiment not only has excellent thermal stability, but is also expected to be suitable for reuse, i.e., recycling, after being discarded. As a recycling method for methacrylic resins, for example, chemical recycling (a method of recovering decomposition oil in the form of decomposition products by thermal decomposition and reusing it as a chemical raw material or fuel) is known. In general, in order to improve the heat resistance and thermal stability of methacrylic resins, operations are performed to introduce a cyclic structure into the molecular structure of the methacrylic resin or to copolymerize monomers having a rigid structure. However, these structures will become impurities for chemical recycling, so they are not preferred. In this regard, it can be predicted that the proportion of structural units derived from methyl methacrylate in the methacrylic resin described in the present embodiment is high, and the yield of monomers recovered in the form of decomposition oil is high, and it can be expected to show good chemical recyclability.

[0066] <Method for producing methacrylic resin>

[0067] The method for producing the methacrylic resin described in the present embodiment includes: in the presence of a non-nitrile azo polymerization initiator (hereinafter also referred to as "polymerization initiator") and a chain transfer agent, a monomer mixture containing 98% by mass or more of methyl methacrylate is polymerized at 100°C or less until the polymerization conversion rate reaches 90% or more. As the method for producing the methacrylic resin, an existing known polymerization method can be used, and free radical polymerization methods such as continuous bulk polymerization, solution polymerization, emulsion polymerization, emulsifier-free (soap-free) emulsion polymerization, and suspension polymerization can be used. Among them, from the viewpoints of the structural design freedom, polymerization simplicity, productivity, etc. of the methacrylic resin, a production method that performs water-based polymerization is preferred, and suspension polymerization and emulsion polymerization are more preferred, and suspension polymerization is further preferred.

[0068] It should be noted that when the methacrylic resin described in the present embodiment is manufactured by water-based polymerization, it is also advantageous from the viewpoint of impurities in the resin. For example, in anionic solution polymerization, an organometallic compound is used as a polymerization initiator, so the metal ions derived from the organometallic compound will remain in the resin by about 100 mass ppm. On the other hand, in water-based polymerization, an organometallic compound is not used as a polymerization initiator, so the total of the residual metal ions in the resin can be made to be less than 100 mass ppm. In the case of water-based polymerization, the Al content in the resin is preferably less than 1 mass ppm, and the Li content is preferably less than 1 mass ppm. In addition, in water-based polymerization, it is not necessary to remove the process of residual metal ions, so it is economically excellent. Furthermore, in water-based polymerization, organic solvents such as aliphatic hydrocarbons and alicyclic hydrocarbons used in anionic solution polymerization are not used, so it is also excellent in terms of environment.

[0069] [Suspension polymerization method]

[0070] In the suspension polymerization method, the methacrylic resin is synthesized in an aqueous suspension mixed with water, a monomer mixture, a dispersant, a polymerization initiator, a chain transfer agent, and optionally other additives. The order in which the components are mixed is not particularly limited. For example, the components can be mixed simultaneously to prepare an aqueous suspension. Alternatively, after mixing water, a polymerization initiator, and optionally other additives to prepare an aqueous solution, a monomer mixture and a chain transfer agent are added, followed by the addition of a dispersant to prepare an aqueous suspension. The mass ratio of the resulting methacrylic resin to water (methacrylic resin / water) is preferably 1.0 / 0.6 to 1.0 / 3.0.

[0071] As the monomer mixture, a mixture having a methyl methacrylate content of 98% by mass or more, preferably 99% by mass or more, more preferably 100% by mass is used.

[0072] As dispersants, there can be listed, for example, poorly water-soluble inorganic salts such as tricalcium phosphate, magnesium pyrophosphate, hydroxyapatite, kaolin, etc.; water-soluble polymers such as polyvinyl alcohol, methylcellulose, polyacrylamide, polyvinyl pyrrolidone, etc. When using poorly water-soluble inorganic salts as dispersants, it is effective to use anionic surfactants such as sodium α-olefin sulfonate and sodium dodecylbenzene sulfonate in combination. These dispersants can be added during the polymerization process as needed.

[0073] As the non-nitrile polymerization initiator, for example, the non-nitrile azo polymerization initiator represented by the above formula (2) can be cited. Among the non-nitrile azo polymerization initiators represented by the above formula (2), from the viewpoints of half-life temperature, cost, etc., at least one selected from 2,2'-azobis(isobutyric acid)dimethyl ester and 1,1'-azobis(cyclohexanecarboxylic acid methyl ester) is preferred.

[0074] It should be noted that, as the polymerization initiator commonly used in the free radical polymerization method, azo polymerization initiator, peroxide polymerization initiator, etc. can be cited. It is known that the free radicals generated by the polymerization initiator, in addition to the addition reaction to the monomer, also undergo hydrogen abstraction reaction in the presence of a substance that easily provides hydrogen. In this regard, since the azo polymerization initiator only generates alkyl radicals, the hydrogen abstraction ability is lower than that of the peroxide polymerization initiator. Here, if the hydrogen abstraction ability of the polymerization initiator is high, then, for example, in the case of using methyl methacrylate as a monomer, the free radicals generated by the polymerization initiator are used to extract hydrogen from the α-methyl group of methyl methacrylate and the methyl group of the ester, and the free radicals on the newly generated α-methyl group and the methyl group of the ester are polymerized, and as a result, it is easy to generate a polymer having a double bond from the monomer structure remaining at the end. Therefore, in the case of using a polymerization initiator with a high hydrogen abstraction ability, there is a tendency that the thermal stability of the resulting methacrylic resin is insufficient. Therefore, in order to obtain a methacrylic resin with high thermal stability, an azo polymerization initiator is more suitable than a peroxide polymerization initiator.

[0075] The hydrogen abstraction ability of the polymerization initiator can be measured by, for example, a radical trapping method using an α-methylstyrene dimer (ie, an α-methylstyrene dimer trapping method).

[0076] The amount of the polymerization initiator is preferably 0.1 mass part or less, more preferably 0.05 mass part or less, and further preferably 0.04 mass part or less relative to 100 mass parts of the total amount of the monomer mixture. The lower limit of the amount of the polymerization initiator is not particularly limited, but from the viewpoint of polymerization speed, it is preferably 0.001 mass part or more relative to 100 mass parts of the total amount of the monomer mixture.

[0077] Examples of the chain transfer agent include primary alkyl mercaptan chain transfer agents such as n-butyl mercaptan, n-octyl mercaptan, n-hexadecyl mercaptan, n-dodecyl mercaptan, and n-tetradecyl mercaptan; secondary alkyl mercaptan chain transfer agents such as sec-butyl mercaptan and sec-dodecyl mercaptan; tertiary alkyl mercaptan chain transfer agents such as tert-dodecyl mercaptan and tert-tetradecyl mercaptan; thioglycolates such as 2-ethylhexyl thioglycolate, ethylene glycol dimercaptoacetate, trimethylolpropane tris(thioglycolate), and pentaerythritol tetra(thioglycolate); thiophenol, tetraethylthiuram disulfide, pentanephenylethane, acrolein, methacrolein, allyl alcohol, carbon tetrachloride, vinyl bromide, styrene oligomers (α-methylstyrene dimer, etc.), terpinolene, etc. These chain transfer agents may be used alone or in combination of two or more.

[0078] Among these chain transfer agents, from the viewpoints of handling properties, stability, thermal stability of the resulting methacrylic resin, etc., alkylthiol chain transfer agents and thioglycolates are preferred. As the alkylthiol chain transfer agent, n-octyl mercaptan is more preferred, and as the thioglycolate, 2-ethylhexyl thioglycolate is more preferred.

[0079] The amount of the chain transfer agent used is 0.10 mol% or more, preferably 0.15 mol% or more, based on the total amount of the monomer mixture. The upper limit of the amount of the chain transfer agent used is not particularly limited, but is preferably 0.45 mol% or less, based on the total amount of the monomer mixture.

[0080] By setting the chain transfer agent to the above-mentioned amount, a methacrylic resin containing a structure derived from the chain transfer agent is obtained. The structure derived from the chain transfer agent refers to: when using, for example, an alkyl mercaptan chain transfer agent or thioglycolate, a structure generated by the reaction of a growing free radical with hydrogen of the alkyl mercaptan chain transfer agent or thioglycolate (in other words, a saturated bond terminal structure); a resin structure generated by the reaction of a sulfhydryl radical generated by the hydrogen of the alkyl mercaptan chain transfer agent or thioglycolate being taken away with a monomer (in other words, a sulfur-containing resin structure), etc. In the methacrylic resin described in the present embodiment, from the viewpoint of the thermal stability of the resin, the amount of sulfur contained in the resin, that is, the amount of bonded sulfur atoms, is preferably 0.05 mol% or more, and more preferably 0.10 mol% or more. Here, the amount of bonded sulfur atoms is the amount relative to the structural unit derived from the monomer in the methacrylic resin.

[0081] In order to reduce the proportion of terminal double bonds of the obtained methacrylic resin and improve thermal stability, the ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is 2.0 or more. The ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is preferably 4.0 or more, more preferably 8.0 or more, and further preferably 10 or more. The upper limit of the ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is not particularly limited, and is preferably 50 or less, for example.

[0082] From the viewpoint of controlling the syndiotacticity of the obtained methacrylic resin and productivity, the polymerization temperature when synthesizing the methacrylic resin is 100° C. or less, preferably 20 to 100° C., more preferably 30 to 98° C., further preferably 50 to 96° C., and particularly preferably 60 to 95° C. After the main reaction is completed in the first stage polymerization, the temperature may be raised to a higher temperature than the first stage to carry out post-polymerization in order to reduce residual monomers.

[0083] It should be noted that, in order to initiate polymerization with a small amount of polymerization initiator, the polymerization reaction is preferably carried out by reducing the amount of dissolved oxygen. The amount of dissolved oxygen in the polymerization raw material is preferably less than 10ppm, more preferably less than 5ppm, further preferably less than 4ppm, and particularly preferably less than 2ppm. By making the amount of dissolved oxygen in this range, there is a tendency that the polymerization reaction is carried out smoothly and the coloring of the molded body of the methacrylic resin is suppressed. As a method for removing dissolved oxygen in the polymerization raw material, for example, inert gases such as nitrogen are continuously conveyed to the reaction vessel before, during and after the temperature is raised to the specified polymerization temperature. In order to remove dissolved oxygen from the raw materials added during the polymerization process, it is preferred that inert gases are also separately introduced into these raw materials.

[0084] In order to smoothly carry out the polymerization reaction, when the monomer mixture contains a polymerization inhibitor, it is preferred to remove the polymerization inhibitor in advance by distillation, alkali extraction or using an adsorbent such as alumina, silica gel, molecular sieve, activated carbon, ion exchange resin, zeolite, acid clay, etc.

[0085] In order to remove the dispersant, the suspension containing the methacrylic resin obtained by suspension polymerization may be subjected to a cleaning operation such as acid cleaning, water cleaning, or alkali cleaning. The number of times these cleaning operations are performed can be selected to be the optimal number considering the work efficiency and the removal efficiency of the dispersant, and may be once or multiple times.

[0086] As a method for separating the methacrylic resin from the suspension containing the methacrylic resin, a conventionally known dehydration method can be adopted, for example, a method using a centrifuge, a method of removing water by suction on a porous belt or a filtration membrane, etc.

[0087] The methacrylic resin in a water-containing state obtained by the above dehydration can be dried and recovered by a conventionally known method. Examples of drying methods include hot air drying in which hot air is sent from a hot air blower, a blast heater, etc. to the tank for drying; vacuum drying in which the system is depressurized and then heated as needed for drying; drum drying in which the obtained methacrylic resin is rotated in a container to disperse water; and spin drying in which the methacrylic resin is dried using centrifugal force. These drying methods may be implemented alone or in combination of two or more.

[0088] [Emulsion polymerization method]

[0089] In the emulsion polymerization method, a methacrylic resin is synthesized in an emulsion in which water, a monomer mixture, an emulsifier, a polymerization initiator, a chain transfer agent, and optionally other additives are mixed.

[0090] As the monomer mixture, a mixture having a methyl methacrylate content of 98% by mass or more, preferably 99% by mass or more, more preferably 100% by mass is used.

[0091] Examples of emulsifiers include anionic surfactants such as alkyl sulfonates, alkylbenzene sulfonates, dialkyl sulfosuccinates, α-olefin sulfonates, naphthalene sulfonate-formaldehyde condensates, alkylnaphthalene sulfonates, N-methyl-N-acyltaurates, phosphate ester salts (polyoxyethylene alkyl ether phosphates, etc.); nonionic surfactants, etc. In addition, examples of the above-mentioned salts include lithium salts, sodium salts, potassium salts, calcium salts, magnesium salts, etc. These emulsifiers may be used alone or in combination of two or more. It should be noted that the emulsifier used in the emulsion polymerization may remain in the final methacrylic resin.

[0092] When the pH of the emulsion deviates from neutrality and becomes acidic or alkaline, an appropriate pH adjuster may be used to prevent hydrolysis of methyl methacrylate as a monomer or a structural unit derived from methyl methacrylate in a methacrylic resin obtained by polymerization. Examples of the pH adjuster include boric acid-potassium chloride-potassium hydroxide, potassium dihydrogen phosphate-sodium hydrogen phosphate, boric acid-potassium chloride-potassium carbonate, citric acid-potassium hydrogen citrate, potassium dihydrogen phosphate-boric acid, and sodium dihydrogen phosphate-citric acid.

[0093] Examples of the polymerization initiator and the chain transfer agent include the same ones as those used in the above-mentioned suspension polymerization method.

[0094] In order to reduce the proportion of terminal double bonds of the obtained methacrylic resin and improve thermal stability, the ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is 2.0 or more. The ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is preferably 4.0 or more, more preferably 8.0 or more, and further preferably 10 or more. The upper limit of the ratio of the total molar amount of the chain transfer agent to the total molar amount of the polymerization initiator is not particularly limited, and is preferably 50 or less, for example.

[0095] The methacrylic resin in solid or powdered form can be obtained by subjecting the latex of the methacrylic resin obtained by emulsion polymerization to heat drying or spray drying, or by subjecting it to a known method (adding a water-soluble electrolyte such as a salt or an acid to solidify it, and then separating the resin component from the aqueous phase after heat treatment to dry it, etc.). The above-mentioned salt is not particularly limited, and is preferably a divalent salt. Specifically, calcium salts such as calcium chloride and calcium acetate; magnesium salts such as magnesium chloride and magnesium sulfate, etc. can be listed. Among these salts, magnesium salts such as magnesium chloride and magnesium sulfate are preferred. During solidification, commonly added additives such as antioxidants and ultraviolet absorbers can be added.

[0096] Before the coagulation operation, the latex is preferably filtered using a filter, a mesh, etc. to remove fine polymerized scales in advance. This can reduce fish eyes, foreign matter, etc. caused by fine polymerized scales when the methacrylic resin is molded.

[0097] In this embodiment, the methacrylic resin obtained by aqueous polymerization may be in the form of a powder, a granule, or a powder and granule containing both powder and granule. Regarding the primary particles constituting the powder, granule, and powder and granule, suspension polymerization is suitable when producing primary particles with an average particle size of about 10 to 1,000 μm, and emulsion polymerization is suitable when producing primary particles with an average particle size of about 50 to 500 nm. The powder, granule, and powder and granule may contain an aggregate of the above primary particles, that is, an aggregate.

[0098] After the polymerization is completed, volatile components such as residual monomers, residual oligomers, and chain transfer agents in the methacrylic resin can be removed as needed. The removal method is not particularly limited, and heating devolatilization is preferred. As a devolatilization method, for example, a treatment based on an extruder with vents can be cited. The vents of the extruder are preferably vacuum vents or open vents, and the screw of the extruder is preferably a twin-shaft screw. Compared with a uniaxial screw, a twin-shaft screw applies greater shear energy to the resin and has a greater degree of surface renewal, so it can be devolatilized efficiently. The barrel heating temperature of the extruder is preferably 150 to 270°C, more preferably 160 to 260°C, and further preferably 180 to 250°C. By setting the barrel heating temperature to below 270°C, the thermal decomposition of the methacrylic resin can be suppressed.

[0099] <Resin composition>

[0100] The resin composition according to this embodiment contains the methacrylic resin according to the above-mentioned embodiment.

[0101] From the viewpoint of further improving the light resistance of the obtained molded body, the resin composition described in the present embodiment preferably contains an ultraviolet absorber. As the ultraviolet absorber, there is no particular limitation, and ultraviolet absorbers that have been blended into various resins can be used. As the ultraviolet absorber, for example, benzotriazole compounds, triazine compounds, oxalylanilide compounds, cyanoacrylate compounds, salicylate compounds, benzophenone compounds, etc. can be listed. Among these, from the viewpoint of the light resistance of the resin composition, triazine compounds are preferably used.

[0102] Examples of the triazine compound include 2,4-diphenyl-6-(2-hydroxyphenyl-4-hexyloxyphenyl)-1,3,5-triazine, 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-(octyloxy)phenol, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]phenol, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol, and 2,4,6-tris(2-hydroxy-4-alkoxy-3-methylphenyl)-1,3,5-triazine. The alkoxy group of 2,4,6-tris(2-hydroxy-4-alkoxy-3-methylphenyl)-1,3,5-triazine is preferably a linear or branched alkoxy group having 1 to 10 carbon atoms. Specific examples of 2,4,6-tris(2-hydroxy-4-alkoxy-3-methylphenyl)-1,3,5-triazine include 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine.

[0103] Among these triazine compounds, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol and 2,4,6-tris(2-hydroxy-4-alkoxy-3-methylphenyl)-1,3,5-triazine are preferred. 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol can be obtained as ADEKASTAB LA-46 (manufactured by ADEKA Corporation). 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine can be obtained as ADEKASTAB LA-F70 (manufactured by ADEKA Corporation). These ultraviolet absorbers may be used alone or in combination of two or more.

[0104] When the resin composition described in the present embodiment contains an ultraviolet absorber, the amount used varies depending on the type of ultraviolet absorber, the conditions of use, etc., and is preferably 0.1 to 5 parts by mass, and more preferably 0.2 to 3 parts by mass relative to 100 parts by mass of methacrylic resin. If the amount of the ultraviolet absorber is 0.1 parts by mass or more, the ultraviolet absorption effect can be improved. In addition, if the amount of the ultraviolet absorber is 5 parts by mass or less, the coloring of the obtained molded body can be suppressed, and the deterioration of transparency caused by the increase in the haze of the molded body can be suppressed.

[0105] In addition, from the viewpoint of further improving the thermal stability and mechanical properties of the obtained molded article, the resin composition according to the present embodiment preferably contains multilayered polymer particles. The multilayered polymer particles are not particularly limited, and known particles can be used as appropriate.

[0106] When the resin composition described in this embodiment contains multilayer structure polymer particles, the blending ratio of the methacrylic resin and the multilayer structure polymer particles varies depending on the use of the molded body, etc., and the blending amount of the methacrylic resin is preferably 30 to 98 parts by mass, and the blending amount of the multilayer structure polymer particles is preferably 2 to 70 parts by mass, relative to 100 parts by mass of the total blending amount of the two components.

[0107] The resin composition described in this embodiment may also contain known additives such as light stabilizers, heat stabilizers, matting agents, light diffusers, colorants, dyes, pigments, antistatic agents, heat ray reflective materials, lubricants, plasticizers, stabilizers, flame retardants, mold release agents, polymer processing aids, fillers, etc.; resins other than methacrylic resins. As resins other than methacrylic resins, for example, styrene resins such as acrylonitrile styrene resins and styrene maleic anhydride resins; polycarbonate resins; polyvinyl acetal resins; acylated cellulose resins; fluorine resins such as polyvinylidene fluoride and polyfluoroalkyl (meth)acrylate resins; silicone resins; polyolefin resins; polyethylene terephthalate resins; polybutylene terephthalate resins, etc.

[0108] In addition, in order to adjust the oriented birefringence of the molded body, the resin composition described in this embodiment may contain inorganic fine particles with birefringence described in Japanese Patent No. 3648201, Japanese Patent No. 4336586, etc., and low molecular weight compounds with birefringence and a molecular weight of 5,000 or less (preferably 1,000 or less) described in Japanese Patent No. 3696649.

[0109] The form of the resin composition according to the present embodiment is not particularly limited, and may be a powder, may be a granular form, may be a powder or granular form including both a powder and a granular form, or may be a pellet form.

[0110] <Molding>

[0111] The methacrylic resin described in this embodiment or the resin composition described in this embodiment can be made into a molded body by a known molding method. As molding methods, for example, melt molding methods such as T-die method (lamination method, co-extrusion method, etc.), inflation method (co-extrusion method, etc.), compression molding method, blow molding method, calendaring molding method, vacuum molding method, injection molding method (insert method, two-color method, pressurization method, Core Back method, sandwich method, etc.); solution casting method, etc.

[0112] <Resin film>

[0113] The resin film described in the present embodiment includes the methacrylic resin described in the above-mentioned present embodiment. The resin film described in the present embodiment is manufactured by, for example, a melt extrusion method using the resin composition described in the above-mentioned present embodiment. When the resin film is manufactured by the melt extrusion method, first, after pre-drying the resin composition described in the present embodiment, it is supplied to an extruder for heating and melting, and supplied to a T-die. Then, the resin composition supplied to the T-die is made into a sheet-like molten resin and extruded, and cooled and solidified using a cooling roller, thereby obtaining a resin film.

[0114] The thickness of the resin film described in this embodiment is, for example, preferably 500 μm or less, more preferably 300 μm or less, and further preferably 200 μm or less. In addition, the thickness of the resin film described in this embodiment is, for example, preferably 10 μm or more, more preferably 30 μm or more, further preferably 50 μm or more, and particularly preferably 60 μm or more. If the thickness of the resin film is within the above range, there is an advantage that the resin film is not easily deformed when vacuum forming is performed using the resin film, and it is not easy to break in the deep drawing portion. Furthermore, there is also an advantage that the optical properties are uniform and a resin film with good transparency can be manufactured.

[0115] The total light transmittance of the resin film according to this embodiment is preferably 85% or more, more preferably 88% or more, and further preferably 90% or more. If the total light transmittance is within the above range, the transparency is high and thus it can be applied to optical applications requiring light transmittance.

[0116] The glass transition temperature of the resin film according to the present embodiment is preferably 110° C. or higher, more preferably 115° C. or higher, and further preferably 120° C. or higher. When the glass transition temperature is within the above range, the heat resistance of the resin film becomes sufficient.

[0117] The haze of the resin film described in this embodiment is preferably 2.0% or less, more preferably 1.5% or less, further preferably 1.3% or less, and particularly preferably 1.0% or less. In addition, the internal haze of the resin film is preferably 1.5% or less, more preferably 1.0% or less, further preferably 0.5% or less, and particularly preferably 0.4% or less. If the haze and internal haze are within the above ranges, the transparency is high, and therefore, it can be applied to optical applications requiring light transmittance. It should be noted that the haze includes the haze inside the film and the haze on the surface (outside) of the film, which are expressed as internal haze and external haze, respectively.

[0118] The YI (Yellow Index) of the resin film according to the present embodiment is preferably 1.2 or less, and more preferably 1.0 or less. When the YI is within the above range, the transparency is high and thus the film can be suitably used in optical applications requiring light transmittance.

[0119] From the viewpoint of further improving light resistance, the resin film of this embodiment preferably contains an ultraviolet absorber. The purpose of the ultraviolet absorber is to improve light resistance by absorbing ultraviolet rays with a wavelength of 400 nm or less. The transmittance of the resin film of this embodiment at a wavelength of 380 nm is preferably in the range of 2 to 30%, more preferably in the range of 4 to 20%, and even more preferably in the range of 5 to 10%.

[0120] The resin film described in the present embodiment can be suitably used as an optical film such as a polarizer protective film. When the resin film described in the present embodiment is used as a polarizer protective film, the optical anisotropy is preferably small. It is particularly preferred that not only the optical anisotropy of the in-plane direction (length direction, width direction) of the resin film is small, but also the optical anisotropy of the thickness direction is small. In other words, it is preferred that the absolute values ​​of the in-plane phase difference and the thickness direction phase difference are both small. For example, when the measurement wavelength is set to 590nm, the absolute value of the in-plane phase difference is preferably less than 20nm, more preferably less than 15nm. In addition, the absolute value of the thickness direction phase difference is preferably less than 50nm, more preferably less than 20nm, and further preferably less than 15nm.

[0121] Phase difference is an index value calculated based on birefringence. The in-plane phase difference (Re) and the thickness direction phase difference (Rth) can be calculated using the following formulas. In an ideal resin film that is completely optically isotropic in three dimensions, the in-plane phase difference Re and the thickness direction phase difference Rth are both 0.

[0122] Re=(nx-ny)×d

[0123] Rth=〔(nx+ny) / 2-nz〕×d

[0124] In the above formula, nx, ny and nz represent the refractive index of each axial direction when the in-plane extension direction (orientation direction of the polymer chain) is set as the X axis, the direction perpendicular to the X axis is set as the Y axis, and the thickness direction of the resin film is set as the Z axis. In addition, d represents the thickness of the resin film, and nx-ny represents the orientation birefringence. It should be noted that the MD direction of the film is set as the X axis, and in the case of a stretched film, the stretching direction is set as the X axis.

[0125] The orientation birefringence value of the resin film according to this embodiment is preferably -5.0×10 -4 ~5.0×10 -4 , more preferably -4.0×10 -4 ~4.0×10 -4 , more preferably -3.8×10 -4 ~3.8×10 -4 When the orientation birefringence is within the above range, birefringence does not occur during molding, and there is a tendency that stable optical characteristics can be obtained.

[0126] (Stretch)

[0127] The resin film according to this embodiment may be further stretched. By stretching the resin film, the mechanical strength of the resin film and the film thickness accuracy can be improved.

[0128] When the resin film according to the present embodiment is stretched, the resin composition according to the present embodiment is temporarily formed into a resin film in an unstretched state, and then uniaxially stretched or biaxially stretched. Thus, a stretched film (uniaxially stretched film or biaxially stretched film) can be manufactured.

[0129] The stretch ratio of the stretched film is not particularly limited and is appropriately determined according to the mechanical strength, surface properties, thickness accuracy, etc. of the stretched film to be manufactured. Depending on the stretching temperature, the stretch ratio is usually preferably selected in the range of 1.1 to 5 times, more preferably in the range of 1.3 to 4 times, and further preferably in the range of 1.5 to 3 times. If the stretch ratio is within the above range, there is a tendency to significantly improve the mechanical properties of the film, such as elongation, tear propagation strength, and rubbing fatigue resistance.

[0130] (use)

[0131] The resin film described in this embodiment can be used for various purposes such as transportation machinery, solar cell components, civil engineering and construction components, daily necessities, electrical and electronic equipment, optical components, medical supplies, etc. In particular, the resin film described in this embodiment has excellent heat resistance and optical properties, and therefore can be suitable for optical purposes. As optical uses, for example, front panels (cover windows) of various display devices, diffusers, polarizer protective films, polarizer protective films, phase difference films, light diffusion films, optical isotropic films, etc. can be listed.

[0132] Among these, the resin film described in the present embodiment can be suitably used as a polarizer protective film or a front panel (cover window) of a display device. When the resin film described in the present embodiment is used as a front panel (cover window) of various display devices, a functional coating layer such as a primer layer and a hard coat layer can be formed on at least one main surface of the resin film as required. In addition, when the resin film described in the present embodiment is used as a polarizer protective film, the resin film described in the present embodiment is pasted with a polarizer to form a polarizing plate. The polarizer is not particularly limited, and any existing known polarizer can be used. The polarizing plate can be used in display devices such as liquid crystal display devices and organic EL display devices.

[0133] Example

[0134] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited to the following Examples. It should be noted that the measurement methods of various physical properties described in Examples and Comparative Examples are as follows.

[0135] (1) Polymerization conversion rate

[0136] The polymerization conversion rate of the methacrylic resin was determined from the ratio of the weight of the methacrylic resin obtained by washing with water and then drying to the weight of the monomer used. The weight of the methacrylic resin obtained by washing with water and then drying was a value obtained by subtracting the weight of the residual monomer in the methacrylic resin obtained by the following analysis. It should be noted that the weight of the methacrylic resins of Comparative Examples 2 and 3 was the weight of the methacrylic resin obtained by precipitation purification after polymerization.

[0137] (Analysis conditions)

[0138] A gas chromatograph (Agilent Technologies, 7890B) was used, and as the analytical column, DB-1 (Agilent Technologies, 0.8 μm film thickness × 0.20 mm inner diameter × 30 m length) was used, and the analysis was performed under the conditions of an injection port temperature of 150°C and a detector temperature of 320°C. The column temperature was set to the following conditions: the temperature was raised from 35°C to 210°C at a heating rate of 30°C / min, then from 210°C to 260°C at a heating rate of 10°C / min, and then from 260°C to 320°C at a heating rate of 20°C / min, and maintained for 3 minutes. A calibration curve was prepared by the internal standard method using chlorobenzene as an internal standard substance, and the polymerization conversion rate was calculated after calculating the residual amount of the monomer in the methacrylic resin.

[0139] (2) Syndiotacticity expressed in terms of triads (rr)

[0140] The methacrylic acid resin was measured using a nuclear magnetic resonance apparatus (AVANCE III 400 MHz, manufactured by Bruker) in a deuterated chloroform solution at 22°C and 16 accumulation times. 1 H-NMR spectrum. Based on the spectrum, the area (X) of the region of 0.60 to 0.95 ppm and the area (Y) of the region of 0.60 to 1.25 ppm when tetramethylsilane (TMS) is set to 0 ppm are measured, and then the syndiotacticity (rr) expressed by triads is calculated using the formula (X / Y)×100.

[0141] (3) Weight average molecular weight (Mw) and the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn)

[0142] The weight average molecular weight (Mw), number average molecular weight (Mn) and the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the methacrylic resin were calculated by a standard polystyrene conversion method using gel permeation chromatography (GPC). Specifically, a sample solution prepared by dissolving 20 mg of a methacrylic resin in 10 mL of tetrahydrofuran was used and the analysis was performed using the following apparatus and conditions.

[0143] Measuring machine: HLC-8220GPC (Tosoh Corporation)

[0144] Detector: RI detector

[0145] Solvent: Tetrahydrofuran

[0146] Guard column: TSKgel guardcolumn SuperHZ-H (Tosoh Corporation)

[0147] Analytical column: TSKgel SuperHZM-H × 2 (Tosoh Corporation)

[0148] Measurement temperature: 40℃

[0149] Standard material: Standard polystyrene (Tosoh Corporation)

[0150] (4) Ratio of terminal double bonds

[0151] For Examples 1 to 5 and Comparative Example 1, as a preliminary treatment, a methacrylic resin was dissolved in dichloromethane, and the solution was added dropwise to methanol to precipitate and purify the resin. The precipitated resin was recovered by suction filtration and dried, and the substance obtained was provided for analysis. For Comparative Examples 2 and 3, the reaction solution after polymerization was added dropwise to methanol for precipitation and purification, and the resin obtained after drying was directly provided for analysis. 20 mg of the dried methacrylic resin was dissolved in 0.6 to 0.7 mL of deuterated chloroform to prepare a solution, and a nuclear magnetic resonance device (made by Bruker, AVANCE NEO 700 MHz) was used for analysis. 1 H-NMR measurement. The measurement temperature was set to 20°C, the number of accumulations was set to 8,192 times, and the ES method, which is one of the solvent elimination methods, was used to eliminate the peak of the methoxy group derived from the methacrylic resin (3.60 ppm, the value when the chemical shift of the peak of the solvent was set to 7.26 ppm). 1The total area (X) of the peaks (5.47 to 5.53 ppm and 6.21 ppm) derived from the terminal double bond of the methacrylic resin and the area (Y) of the peak (0.5 to 1.25 ppm) derived from the α-methyl group of the methacrylic resin were measured by H-NMR spectrum, and then the ratio of the terminal double bond of the methacrylic resin was calculated by the formula [(3×X) / (2×Y)]×100.

[0152] (5) Glass transition temperature (Tg)

[0153] The glass transition temperature of the methacrylic resin is measured by the following method. As a prior treatment, a thermogravimetric analyzer (manufactured by Hitachi High-Technologies Corporation, STA7200) is used for heat treatment for the purpose of removing the residual monomers and decomposition products of the polymerization initiator in the methacrylic resin. Specifically, the heat treatment is carried out under the following conditions: under a nitrogen gas flow of 200 mL / min, the temperature is increased from 40°C to 270°C at a heating rate of 10°C / min, and maintained at 270°C for 2.0 to 2.5 minutes. The glass transition temperature (Tg) of the methacrylic resin after the heat treatment is measured using a differential scanning calorimeter (DSC; manufactured by Hitachi High-Technologies Corporation, DSC7000X). First, DSC measurement was performed under the following conditions: the first temperature rise was performed at a nitrogen flow rate of 40 mL / min, the temperature was raised from 40° C. to 160° C. at a heating rate of 10° C. / min, and after cooling to 40° C., the temperature was raised from 40° C. to 160° C. at a heating rate of 10° C. / min. The second temperature rise was performed. And, the midpoint glass transition temperature (the intersection temperature of the straight line having the same distance in the vertical axis direction from both the straight line obtained by extending the baseline before the inflection point toward the high temperature side and the straight line obtained by extending the baseline after the inflection point toward the low temperature side and the curve of the step-like change part of the glass transition) was read from the DSC curve measured during the second temperature rise.

[0154] (6) Retention thermal stability

[0155] The retention thermal stability of methacrylic resin was evaluated using a thermogravimetric analyzer (manufactured by Hitachi High-Technologies, STA7200). First, for the purpose of removing the decomposition products of the residual monomers and polymerization initiators in the methacrylic resin, heat treatment was performed under the following conditions: under a nitrogen gas flow of 200 mL / min, the temperature was raised from 40°C to 270°C at a heating rate of 10°C / min, and kept at 270°C for 2.0 to 2.5 minutes. Then, the mass change was recorded under the following conditions: after cooling to 40°C, the temperature was raised from 40°C to 280°C at a heating rate of 10°C / min, and kept at 280°C for 30 minutes. The mass of the sample when the temperature reached 280°C was set as X 0, the mass when kept at 280℃ for 15 minutes is set as X 15 , according to the formula 〔(X 0 -X 15 ) / X 0 The retention thermal stability was evaluated by calculating the mass reduction rate by 〕×100.

[0156] (7) Bonded sulfur atomic weight

[0157] The amount of bonded sulfur atoms of methacrylic resin is obtained by the following operation. As a preliminary treatment, methacrylic resin is dissolved in dichloromethane, and the solution is added dropwise to methanol to precipitate and purify the resin. The precipitated resin is recovered and dried by suction filtration, and the material obtained is provided for analysis. An appropriate amount of dried methacrylic resin is accurately weighed and fixed to volume, and is set in an automatic sample combustion device (Nittoseiko Analytech, AQF-2100), decomposed at high temperature, and the generated gas is absorbed by ultrapure water containing aqueous hydrogen peroxide and hydrazine hydrate. Using the resulting liquid (decomposed gas aqueous solution), sulfate ions are quantified using an ion chromatograph (Thermo Fisher Scientific, IntegrionRFIC, column: AG18-4μm, AS18-4μm). Next, the mass Wp (mass %) of sulfur atoms per unit mass of the dried methacrylic resin is calculated. Furthermore, the amount Sp (mol %) of bonded sulfur atoms is calculated using the following formula.

[0158] Sp=Wp×(100 / 32)

[0159] (8) Haze measurement

[0160] The haze of the stretched resin film was measured using a haze meter (Suga Test Instruments, HZ-V3) in accordance with JIS K7136. In addition, the two sides of the resin film were sandwiched with glycerin and glass in sequence and the same measurement was performed, and the value obtained was set as the internal haze. The obtained result was converted into a value equivalent to a film thickness of 40 μm.

[0161] (9) Total light transmittance

[0162] The total light transmittance of the stretched resin film was measured using a haze meter (HZ-V3 manufactured by Suga Test Instruments) in accordance with JIS K7361-1.

[0163] (10) Transmittance at a wavelength of 380 nm

[0164] The light transmittance of the stretched resin film at a wavelength of 380 nm was measured using an ultraviolet-visible spectrophotometer (V-560, manufactured by JASCO Corporation).

[0165] (11)YI

[0166] The YI of the stretched resin film was measured using a spectrocolorimeter (manufactured by Suga Test Instruments, SC-P) in accordance with JIS K7373. The obtained result was converted into a value corresponding to a film thickness of 40 μm.

[0167] <Example 1>

[0168] 170 parts by mass of deionized water, 0.10 parts by mass of disodium hydrogen phosphate as a suspension aid, and 0.037 parts by mass of 2,2'-azobis(isobutyric acid)dimethyl ester (V-601 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were placed in a 2-liter glass reactor equipped with a three-way backward blade stirrer. The aqueous solution in the reactor was stirred at 550 rpm while nitrogen (oxygen concentration was 0.2 ppm) was passed through to replace the air in the reactor. Then, a monomer solution containing 100 parts by mass of methyl methacrylate (MMA) and 0.322 parts by mass of n-octyl mercaptan (n-OM) as a chain transfer agent was added to the reactor. Next, 0.375 parts by mass of METOLOSE 60SH-50 (hydroxypropyl methylcellulose manufactured by Shin-Etsu Chemical Co., Ltd.), a water-soluble polymer, was added to the reactor as a dispersant. After that, after stirring for 30 minutes, the liquid temperature in the reactor was raised to 81°C to start polymerization. After the monomer was reacted at 81°C for 4.5 hours, the liquid in the reactor was heated to 95°C. The reaction solution was stirred at the same temperature for 1 hour to terminate the polymerization. The average temperature of the entire polymerization from the time the temperature was raised to 81°C to the end of the polymerization was 84°C. The obtained resin was washed with deionized water in an amount 3.9 times the amount of the resin and dried to obtain a beaded methacrylic resin. The physical properties of the obtained methacrylic resin are shown in Table 1.

[0169] <Example 2>

[0170] In a 2-liter glass reactor equipped with a three-way backward blade stirrer, 170 parts by mass of deionized water, 0.10 parts by mass of disodium hydrogen phosphate as a suspension aid, and 0.037 parts by mass of 2,2'-azobis(isobutyric acid) dimethyl ester (V-601 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were placed. The aqueous solution in the reactor was stirred at 550 rpm while nitrogen (oxygen concentration was 0.2 ppm) was passed through, and after replacing the air in the reactor, a monomer solution containing 100 parts by mass of methyl methacrylate (MMA) and 0.220 parts by mass of n-octyl mercaptan (n-OM) as a chain transfer agent was added to the reactor. Next, 0.375 parts by mass of METOLOSE 60SH-50 (hydroxypropyl methylcellulose manufactured by Shin-Etsu Chemical Co., Ltd.), a water-soluble polymer, was added to the reactor as a dispersant. After that, after stirring for 30 minutes, the liquid temperature in the reactor was raised to 78°C to start polymerization. After the monomers were reacted at 78°C for 6.5 hours, the liquid in the reactor was heated to 93°C. The reaction solution was stirred at the same temperature for 1 hour to terminate the polymerization. The average temperature of the entire polymerization from the time the temperature was raised to 78°C to the end of the polymerization was 80°C. The obtained resin was washed with deionized water in an amount 2.9 times the amount of the resin and dried to obtain a beaded methacrylic resin. The physical properties of the obtained methacrylic resin are shown in Table 1.

[0171] <Example 3>

[0172] 150 parts by mass of deionized water, 0.140 parts by mass of tricalcium phosphate as a dispersant, 0.0075 parts by mass of sodium α-olefin sulfonate, and 0.30 parts by mass of sodium chloride were placed in a 4-liter glass reactor equipped with an H-type stirring blade type stirrer. While stirring the aqueous solution in the reactor at 250 rpm, nitrogen gas (oxygen concentration of 0.2 ppm) was introduced to replace the air in the reactor, and then a monomer solution containing 100 parts by mass of methyl methacrylate (MMA), 0.289 parts by mass of n-octyl mercaptan (n-OM) as a chain transfer agent, and 0.037 parts by mass of 2,2'-azobis(isobutyric acid) dimethyl ester (V-601 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator was added to the reactor. Thereafter, the liquid temperature in the reactor was raised to 80°C to start polymerization. After 1 hour and 40 minutes had passed since the start of polymerization, 0.10 parts by mass of tricalcium phosphate was additionally added to the reaction solution. Thereafter, the temperature of the liquid in the reactor was raised in stages and adjusted to 87°C after 4 hours from the start of polymerization. At this time, 0.22 parts by mass of tricalcium phosphate was added to the reaction solution. Furthermore, after 10 minutes, 0.037 parts by mass of 2,2'-azobis(isobutyric acid)dimethyl ester was added to the reaction solution. Next, the temperature of the liquid in the reactor was raised to 95°C, and the polymerization was terminated at the time when stirring was continued at 95°C for 1 hour and 30 minutes. The average temperature of the entire polymerization from the time the temperature was raised to 80°C to the end of the polymerization was 87°C. Acid washing was performed using 1 equivalent hydrochloric acid in an amount of 0.1 times the weight ratio relative to the amount of the fed monomer, and washed with water and dried to obtain a beaded methacrylic resin. The physical properties of the obtained methacrylic resin are shown in Table 1.

[0173] The obtained methacrylic resin was extruded at a resin temperature of 255° C. using an intermeshing co-rotating twin-screw extruder (manufactured by TECHNOVEL, KZW15TWIN-45MG, L / D=45) having a diameter of 15 mm. The resin extruded in the form of strands from a die head provided at the outlet of the extruder was cooled in a water tank and pelletized in a pelletizer to obtain a resin composition.

[0174] The obtained resin composition was dried at 90° C. for 4 hours and then extruded at a resin temperature of 240° C. using an intermeshing co-rotating twin-screw extruder (manufactured by TECHNOVEL, KZW15TWIN-45MG, L / D=45) having a T-die with a diameter of 15 mm at the extruder outlet. The sheet-like molten resin extruded from the T-die was cooled with a cooling roll to obtain a resin film with a width of 130 mm and a thickness of 160 μm.

[0175] A small piece of 100 mm × 100 mm was cut from the obtained resin film in a manner that both sides were parallel to the extrusion direction. The small piece was placed in a pantograph biaxial stretching device and biaxially stretched at 137°C in a direction parallel to the extrusion direction by 2 times and in a direction perpendicular to the extrusion direction by 2 times. The stretching speed in each direction was set to 100 mm / min. Thereafter, the film was taken out at room temperature and quenched to obtain a resin film with a thickness of 39 μm. The physical properties of the resin film are shown in Table 1.

[0176] <Example 4>

[0177] 0.7 parts by mass of an ultraviolet absorber (ADEKASTAB LA-F70 manufactured by ADEKA Corporation) was mixed with 100 parts by mass of the methacrylic resin obtained in Example 3. The mixture was kneaded and extruded at 255° C. using a 15 mm diameter intermeshing co-rotating twin-screw extruder (KZW15TWIN-45MG manufactured by TECHNOVEL Corporation, L / D=45). The resin extruded in the form of strands from the die provided at the exit of the extruder was cooled in a water tank and pelletized in a pelletizer to obtain a resin composition.

[0178] The obtained resin composition was used to obtain a resin film having a width of 130 mm and a thickness of 160 μm in the same manner as in Example 3. Furthermore, the resin film was subjected to simultaneous biaxial stretching in the same manner as in Example 3 to obtain a resin film having a thickness of 39 μm. The physical properties of the resin film are shown in Table 1.

[0179] <Example 5>

[0180] 150 parts by mass of deionized water, 0.400 parts by mass of tricalcium phosphate as a dispersant, 0.0075 parts by mass of sodium α-olefin sulfonate, and 0.30 parts by mass of sodium chloride were added to a glass sample bottle. The aqueous solution in the sample bottle was stirred with a stirrer, and a monomer solution containing 100 parts by mass of methyl methacrylate (MMA), 0.093 parts by mass of 2,2'-azobis(isobutyric acid) dimethyl ester (V-601 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 0.289 parts by mass of n-octyl mercaptan (n-OM) as a chain transfer agent was added thereto. After the suspension in the sample bottle was transferred to a 120mL metal pressure-resistant container equipped with a semicircular stirrer, nitrogen (oxygen concentration of 0.2ppm) was introduced while stirring at 150rpm to replace the air in the reaction container. Thereafter, the liquid temperature in the reaction container was raised to 97°C, polymerization was started, and the polymerization was terminated when it was reacted for 5 hours and 20 minutes. The average temperature of the entire polymerization from the time of heating to 97°C to the end of the polymerization was 97°C. The liquid in the reaction vessel was cooled and discharged, and acid washing was performed using 1N hydrochloric acid in an amount of 0.5 times the weight ratio of the charged monomer, and then washed with water and dried to obtain bead-shaped methacrylic resin. The physical properties of the obtained methacrylic resin are shown in Table 1.

[0181] <Comparative Example 1>

[0182] 170 parts by mass of deionized water, 0.10 parts by mass of disodium hydrogen phosphate as a suspension aid, and 0.040 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) (V-65, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were placed in a 2-liter glass reactor equipped with a three-way backward blade stirrer. The aqueous solution in the reactor was stirred at 550 rpm while nitrogen (oxygen concentration was 0.2 ppm) was passed through, and after replacing the air in the reactor, a monomer solution containing 100 parts by mass of methyl methacrylate (MMA) and 0.322 parts by mass of n-octyl mercaptan (n-OM) as a chain transfer agent was added to the reactor. Next, 0.375 parts by mass of METOLOSE 60SH-50 (hydroxypropyl methylcellulose, manufactured by Shin-Etsu Chemical Co., Ltd.), a water-soluble polymer as a dispersant, was added to the reactor. After that, after stirring for 30 minutes, the liquid temperature in the reactor was raised to 70°C to start polymerization. After the monomers were reacted at 70°C for 6 hours, the liquid in the reactor was heated to 95°C. The reaction solution was stirred at the same temperature for 1 hour to terminate the polymerization. The average temperature of the entire polymerization from the time the temperature was raised to 70°C to the end of the polymerization was 74°C. The obtained resin was washed with deionized water in an amount 7.0 times the amount of the resin and dried to obtain a beaded methacrylic resin. The physical properties of the obtained methacrylic resin are shown in Table 1.

[0183] <Comparative Example 2>

[0184] 1800 parts by mass of o-dichlorobenzene as a polymerization solvent was added to a 120 mL metal pressure-resistant container equipped with a U-shaped stirrer, and further, a monomer liquid containing 100 parts by mass of methyl methacrylate (MMA), 0.037 parts by mass of 2,2'-azobis(isobutyric acid) dimethyl ester (V-601 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 0.289 parts by mass of n-octyl mercaptan (n-OM) as a chain transfer agent was added. Nitrogen (oxygen concentration of 50 ppm) was introduced into the reaction container to replace the air in the reaction container, and then the temperature of the liquid in the reaction container was raised to about 140°C while stirring to start polymerization. The polymerization was terminated when the monomer was allowed to react at about 140°C for further 6 hours. The average temperature of the entire polymerization from the time of heating to about 140°C to the end of polymerization was 142°C. The liquid in the reaction container was cooled and discharged, and the reaction liquid was dropped into methanol to precipitate the resin. The precipitated resin was recovered by filtration and then dried to obtain a methacrylic resin. Table 1 shows the physical properties of the obtained methacrylic resin.

[0185] <Comparative Example 3>

[0186] 339 parts by mass of methanol as a polymerization solvent was added to a 2-liter glass reactor equipped with a three-way backward blade type stirrer, and a monomer solution containing 100 parts by mass of methyl methacrylate (MMA) and 2.46 parts by mass of 2,2'-azobis(isobutyric acid) dimethyl ester (V-601 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator was further added. The aqueous solution in the reactor was stirred at 220 rpm, and nitrogen (oxygen concentration was 0.2 ppm) was passed into the reaction container. After replacing the air in the reaction container, the liquid temperature in the reaction container was raised to 60°C while stirring to start polymerization. The polymerization was terminated when the monomer was allowed to react at 60°C for further 3 hours. At this time, the generated resin precipitated to the bottom of the reaction container. The average temperature of the entire polymerization from the temperature increase to 60°C to the end of the polymerization was 60°C. After cooling the liquid in the reaction vessel, the resin precipitated to the bottom of the reaction vessel was dissolved in 400 parts by mass of chloroform, and the chloroform solution was dropped into 2500 parts by mass of methanol to precipitate the resin again. The reprecipitated resin was recovered by filtration and then dried to obtain a methacrylic resin. The physical properties of the obtained methacrylic resin are shown in Table 1.

[0187] [Table 1]

[0188]

[0189] As shown in Table 1, compared with Comparative Example 1 using 2,2'-azobis(2,4-dimethylvaleronitrile) as a nitrile azo polymerization initiator at the same usage ratio (mol%), Example 1 using 2,2'-azobis(isobutyric acid)dimethyl ester as a non-nitrile azo polymerization initiator has a smaller weight loss rate when kept at 280°C for 15 minutes and has high retention thermal stability. In addition, Example 2, in which the usage ratio (mol%) of 2,2'-azobis(isobutyric acid)dimethyl ester as a non-nitrile azo polymerization initiator is the same as that of Example 1 and the usage ratio (mol%) of n-octyl mercaptan (n-OM) as a chain transfer agent is less than that of Example 1, has a smaller weight loss rate when kept at 280°C for 15 minutes and has high retention thermal stability than Comparative Example 1 using 2,2'-azobis(2,4-dimethylvaleronitrile) as a nitrile azo polymerization initiator. Furthermore, in Example 3, in which the ratio (mol%) of 2,2'-azobis(isobutyric acid)dimethyl ester used as a non-nitrile azo polymerization initiator is higher than that of Example 1, and the ratio (mol%) of n-octyl mercaptan (n-OM) used as a chain transfer agent is lower than that of Example 1, the weight loss rate when kept at 280°C for 15 minutes is smaller than that of Comparative Example 1 using 2,2'-azobis(2,4-dimethylvaleronitrile) as a nitrile azo polymerization initiator, and the retention thermal stability is higher. In addition, when Example 3 is compared with Example 4, in Example 4 to which an ultraviolet absorber is added, the light transmittance at a wavelength of 380nm is lower than that of Example 3. In addition, regarding Example 5, in which the usage ratio (mol %) of 2,2'-azobis(isobutyric acid)dimethyl ester as a non-nitrile azo polymerization initiator is greater than that of Example 3 and the average polymerization temperature is higher than that of Example 3, the weight loss rate when kept at 280°C for 15 minutes is smaller than that of Comparative Example 1 using 2,2'-azobis(2,4-dimethylvaleronitrile) as a nitrile azo polymerization initiator, and the retention thermal stability is higher.

[0190] It should be noted that in Comparative Example 2, in which the polymerization was carried out under the condition of an average polymerization temperature exceeding 100°C, although 2,2'-azobis(isobutyric acid)dimethyl ester was used as a non-nitrile azo polymerization initiator at the same usage ratio (mol %) as in Examples 1 and 2, the weight loss rate when kept at 280°C for 15 minutes was still large and the retention thermal stability was poor compared to Examples 1 and 2. In addition, in Comparative Example 3, in which the resin was polymerized without using a chain transfer agent, the proportion of terminal double bonds was large compared to Examples 1 to 5, and the weight loss rate when kept at 280°C for 15 minutes was also large, and the retention thermal stability was poor.

Claims

1. A methacrylic resin, wherein The proportion of structural units derived from methyl methacrylate is 98% by mass or more, The syndiotacticity expressed as triad is 55% or more, The methacrylic resin includes a terminal structure represented by the following formula (1) derived from a polymerization initiator, The ratio of the terminal double bond to the structural unit derived from methyl methacrylate is less than 0.020 mol%, In formula (1), R 1 , R 2 and R 3 Each independently represents an alkyl group, a substituted alkyl group, an ester group or an amide group, wherein R 1 , R 2 and R 3 At least one of represents an ester group or an amide group, R 1 , R 2 and R 3 Two of them may be bonded to each other to form an alicyclic structure, and * represents a bond connecting to a structural unit derived from a monomer. 2 . The methacrylic resin according to claim 1 , which has a thermal weight loss rate of less than 2.5% when exposed to 280° C. for 15 minutes in a nitrogen atmosphere.

3. The methacrylic resin according to claim 1 or 2, wherein The terminal structure represented by the formula (1) is a terminal structure derived from at least one selected from 2,2′-azobis(isobutyric acid)dimethyl ester and 1,1′-azobis(cyclohexanecarboxylic acid methyl ester). 4 . The methacrylic resin according to claim 1 , wherein the weight average molecular weight (Mw) measured by gel permeation chromatography (GPC) is 50,000 to 200,000. The methacrylic resin according to claim 1 or 2, wherein the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) measured by gel permeation chromatography (GPC) is 1.6 to 2.

5.

6. A method for producing a methacrylic resin, comprising: A polymerization step of polymerizing a monomer mixture containing 98% by mass or more of methyl methacrylate at 100° C. or less in the presence of a non-nitrile azo polymerization initiator and a chain transfer agent until the polymerization conversion rate reaches 90% or more, The amount of the chain transfer agent used is 0.10 mol% or more relative to the total amount of the monomer mixture. The ratio of the total molar amount of the chain transfer agent to the total molar amount of the non-nitrile azo polymerization initiator is 2.0 or more.

7. The method for producing a methacrylic resin according to claim 6, wherein: In the polymerization step, aqueous polymerization is performed.

8. The method for producing a methacrylic resin according to claim 6 or 7, wherein: The non-nitrile azo polymerization initiator includes at least one selected from 2,2′-azobis(isobutyric acid)dimethyl ester and 1,1′-azobis(cyclohexanecarboxylic acid methyl ester). 9 . A resin composition comprising the methacrylic resin according to claim 1 . 10 . The resin composition according to claim 9 , comprising an ultraviolet absorber. 11 . A resin film comprising the methacrylic resin according to claim 1 or 2 . The resin film according to claim 11 , comprising an ultraviolet absorber.

13. The resin film according to claim 11, wherein The resin film is a polarizer protective film.

14. A polarizing plate comprising a polarizer and the resin film according to claim 11 laminated together. 15 . A display device comprising the polarizing plate according to claim 14 .

Citation Information

Patent Citations

  • Methacrylic resin, methacrylic resin composition, and molded body

    WO2019088025A1